2002
DOI: 10.1006/dbio.2002.0591
|View full text |Cite
|
Sign up to set email alerts
|

Epithelia–Mesenchyme Interaction Plays an Essential Role in Transdifferentiation of Retinal Pigment Epithelium of silver Mutant Quail: Localization of FGF and Related Molecules and Aberrant Migration Pattern of Neural Crest Cells during Eye Rudiment Formation

Abstract: Homozygotes of the quail silver mutation, which have plumage color changes, also display a unique phenotype in the eye: during early embryonic development, the retinal pigment epithelium (RPE) spontaneously transdifferentiates into neural retinal tissue. Mitf is considered to be the responsible gene and to function similarly to the mouse microphthalmia mutation, and tissue interaction between RPE and surrounding mesenchymal tissue in organ culture has been shown to be essential for the initiation of the transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 47 publications
(44 reference statements)
1
19
0
Order By: Relevance
“…The role of HSPG in developmental stage of the embryonal eye [31] and GAG distribution in the different eye part of vertebrates [32] have been described, however, the disaccharide composition of adult vertebrate eye HS not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The role of HSPG in developmental stage of the embryonal eye [31] and GAG distribution in the different eye part of vertebrates [32] have been described, however, the disaccharide composition of adult vertebrate eye HS not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…While the molecular basis for this loss in the competence of the RPE to regenerate retina in birds and mammals is not known, Araki et al (2002) reported that an interaction with the adjacent extra-ocular mesenchyme is critical for limiting RPE transdifferentiation. In addition, Fuhrmann et al (2000) reported that an activin-like factor released from the extra-ocular mesenchyme during development is necessary and sufficient for the induction of the RPE fate in the proximal part of the optic vesicle.…”
Section: 2mentioning
confidence: 97%
“…The avian mutant Silver quail exhibits transdifferentiation of RPE in a limited portion, which indicates that some specific tissue interactions between RPE and other neighboring tissues must take place in that area. When the RPE layer from Silver mutant embryos was isolated from surrounding tissues and placed into culture, transdifferentation was only observed when recombined with choroid (Araki et al, 2002; Araki et al, 1998). In frog, the choroid contains high concentrations of the basement membrane component laminin and in high levels of laminin, dissociated RPE cells migrate, loose their pigment, start to proliferate extensively and assume a neuroepithelial phenotype (Reh and Nagy, 1987).…”
Section: Overview Of Early Eye Development and Rpe Specificationmentioning
confidence: 99%